ANALYSIS OF THE EFFECT OF FUNDAMENTAL FACTORS AND ITS IMPLICATIONS ON DIVIDEND PAYOUT RATIO - Sawukir, Sawukir (Universitas Pamulang, 2020)
Fundamental factors have a strong influence on Earning Per Share because fundamental factors indicate the company's financial performance. The purpose of this study was to determine the effect of current ratio (CR), return on equity (ROE) and debt to equity ratio (DER) on earnings per share (EPS) and its implications for the dividend payout ratio (DPR) in pharmaceutical companies in the Malaysian stock exchange period 2012 - 2016 partially and simultaneously.The study was conducted using descriptive statistical methods and panel data regression methods. The sampling technique used was purposive sampling with a sample of 40 samples. The research data is secondary data obtained from www.bursamalaysia.com for the period 2012-2016. Testing the research hypothesis using a common effect model with the e-views version 9 application tool.The results in this study show that the Growth of Current Ratio, Return on Equity, Debt to Equity Ratio, Earning Per Share and Dividend Payout Ratio in pharmaceutical companies fluctuate every year. In Partial Current Ratio there is no significant effect on the variable Earning Per Share. In Partial Return On Equity has a significant effect on Earning Per Share. In real terms Debt to Equity Ratio has no significant effect on Earning Per Share. Simultaneously and together the variables Current Ratio, Return On Equity and Debt To Equity Ratio have a significant effect on Earning Per Share. Partially Earning Per Share has a significant effect on Dividend Payout Ratio.